2014
DOI: 10.1159/000368318
|View full text |Cite
|
Sign up to set email alerts
|

Central Adrenal Insufficiency Could Not Be Confirmed by Measurement of Basal Serum DHEAS Levels in Pubertal Children

Abstract: Background: Central adrenal insufficiency (CAI) is due to a decrease of CRH and/or ACTH secretion. ACTH-dependent dehydroepiandrosterone sulphate (DHEAS) has been postulated as a possible marker of adrenal function in adult patients. Aims: To evaluate the usefulness of basal serum DHEAS determination to diagnose CAI in pubertal patients with a suspected diagnosis of CAI. Methods: Ninety-four pubertal patients suspected of having CAI were divided into two groups according to sufficient (group 1) or insufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The hypothalamicpituitary thyroid and adrenal axes were evaluated by determining serum basal T4, T3, fT4, and TSH, thyroid antibodies, and morning ACTH and cortisol levels, and/or the low-dose ACTH test, respectively [22] . Patients were assessed periodically at least once a year.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothalamicpituitary thyroid and adrenal axes were evaluated by determining serum basal T4, T3, fT4, and TSH, thyroid antibodies, and morning ACTH and cortisol levels, and/or the low-dose ACTH test, respectively [22] . Patients were assessed periodically at least once a year.…”
Section: Methodsmentioning
confidence: 99%
“…Dehydroepiandrosterone sulfate (DHEAS) is exclusively produced in the adrenal reticularis zone by ACTH stimulus ( 1 , 2 ). Some studies have suggested that impairment of adrenal androgen secretion precedes glucocorticoid deficiency in patients with CAI ( 45 - 47 ). Its mechanisms are not fully understood, but some insights are presented by Topor and cols.…”
Section: When?mentioning
confidence: 99%
“…DHEAS has a longer half-life (about 20 h) and lesser diurnal variation than cortisol ( 47 ), which can be advantageous. These two factors provide serum levels of DHEAS all day long (unlike cortisol).…”
Section: When?mentioning
confidence: 99%